Cara Berpikir Visual Siswa SMA dalam Memahami Masalah Dimensi Tiga - Fran Susanto (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to describe the visual thinking of high school students in understanding three-dimensional problems. This research is a descriptive research with a qualitative approach. Two students with medium and high mathematical skills of the female gender were selected as research subjects. Data was collected by giving three-dimensional problem-solving tasks according to Polya's steps and interviews. Students' visual thinking is described based on seeing, recognizing, imagining, and showing. The results of the study show that at the comprehension stage, students with medium and high mathematical skills do looking and seeing, recognizing and imagining at the planning stage, and showing the steps to implement the problem-solving plan appropriately but in a different way, students with medium ability use more concise steps and vice versa for high-ability students; At the re-examination stage, the two subjects showed (showing) the conclusion of the solution solution, but did not show (showing) re-checking.